2017
DOI: 10.1159/000475500
|View full text |Cite
|
Sign up to set email alerts
|

The Kidney in Bardet-Biedl Syndrome: Possible Pathogenesis of Urine Concentrating Defect

Abstract: Background: The ciliopathies are a growing number of disorders caused by mutations in genes involved in the function of the primary cilium. Bardet-Biedl syndrome (BBS) belongs to this group of disorders. In this setting, kidney dysfunction is highly variable, and urine concentrating defect, a common feature of multiple ciliopathies, has been described as the most frequent defect. Here we review the mechanism of urine concentration and describe the possible mechanism underling this defect in ciliopathies and es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 48 publications
1
16
0
Order By: Relevance
“… 60 Kidney-specific Bbs10 KO mice did not exhibit structural and/or functional kidney defects, suggesting that systemic rather than local factors affect kidney function. 95 Finally, Loktev et al. 56 described the phenotype of BBPI10/BBS18 null mice; obesity, hyperphagia, retinal degeneration, and male sterility recapitulated most human findings.…”
Section: Genetics Of Bbsmentioning
confidence: 94%
“… 60 Kidney-specific Bbs10 KO mice did not exhibit structural and/or functional kidney defects, suggesting that systemic rather than local factors affect kidney function. 95 Finally, Loktev et al. 56 described the phenotype of BBPI10/BBS18 null mice; obesity, hyperphagia, retinal degeneration, and male sterility recapitulated most human findings.…”
Section: Genetics Of Bbsmentioning
confidence: 94%
“…Urine Aquaporin 2 (u-AQP2) excretion has been used as marker of its abundance on the apical membrane of principal collecting duct cells [24]. Interestingly, our study indicated that after long term water restriction, in hyposthenuric BBS patients u-AQP2 excretion was not different compared with healthy volunteers, indicating that the inability to reach the maximum urine osmolality in BBS patients is not the consequence of impaired AQP2 trafficking [10, 25]. However, after acute stimuli, namely acute water loading and dDAVP infusion, BBS patients showed a blunted response of u-AQP2 excretion.…”
Section: Renal Abnormalities In Bbsmentioning
confidence: 89%
“…Moreover, the increased levels of uric acid in humans might counterbalance the loss of ascorbate. Indeed, uric acid has ‘protective’ properties such as (i) anti-oxidant activity (possibly replacing the loss of ascorbate synthesis) [5, 7], (ii) antinatriuretic and vascular effects mediating blood pressure homeostasis in low-salt environments [4], (iii) neuroprotection, particularly on dopaminergic neurons [8], (iv) modulator of the gut microbiome, whose composition is therefore different in humans from other animals [9, 10] a marker of effective blood volume and antidiuretic hormone levels [11, 12] and an accurate and reliable marker of kidney function [13]. …”
Section: Discovery Of Uric Acid In the Urine And Its Evolutionary Meamentioning
confidence: 99%